Analisis Proses Berpikir Siswa dalam Menyelesaikan Masalah SPLDV Kelas VIII Di SMPN 1 Pringgarata Tahun Pelajaran 2022/2023 - Laelatul Kurnia; Ahmad Muzaki; Eliska Juliangkary (Jurnal Kependidikan Ki Hajar Dewantara, 2024)
This research aims to describe students' thinking processes based on the Wallas stage in solving mathematics problems in class VIII of SMPN 1 Pringgarata for the 2022/2023 academic year. The method used in this research is descriptive with a qualitative approach. The location of this research is at SMPN 1 Pringgarata. The subjects used in this research were 6 students who had high, medium and low categories based on their final semester test scores in mathematics. The instruments used in this research were 3 essay questions on two-variable linear equation systems in the form of story questions. Data collection techniques include giving tests, interviews and documentation. The data analysis technique used in this research uses 3 stages, namely data reduction, data presentation and conclusion drawing. The research results showed that in the initial stage or preparation stage for S1 to S6 subjects showed an attitude of detachment, reflection, re-reading questions and remembering material that had been received previously so that all subjects reached the incubation indicators. the third stage is illumination where at this stage the subject finds ideas in solving the problem but the object cannot be completed correctly and completely because of errors in modeling it into a mathematical model, errors in calculating, the last stage is verification, where at this stage almost all subjects provide wrong answer and no student effort in correcting the wrong answer except subject S1, namely giving the correct answer to questions number 1 to 3.